2021
DOI: 10.1186/s13287-021-02350-5
|View full text |Cite
|
Sign up to set email alerts
|

Conversion of stem cells from apical papilla into endothelial cells by small molecules and growth factors

Abstract: Objectives Recently, a new strategy has been developed to directly reprogram one cell type towards another targeted cell type using small molecule compounds. Human fibroblasts have been chemically reprogrammed into neuronal cells, Schwann cells and cardiomyocyte-like cells by different small molecule combinations. This study aimed to explore whether stem cells from apical papilla (SCAP) could be reprogrammed into endothelial cells (ECs) using the same strategy. Ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…Besides, the expression levels of IL-1β and TNF-α decreased within time in each group. On the other hand, IL-10 is a pro-healing cytokine, which can inhibit the function of T helper 1 (Th1) cell and reduce the production of pro-inflammatory cytokines [ 48 ]. The expression of IL-10 gradually increased over time, and iTE-scaffold group expressed higher IL-10 than NC and P-scaffold groups (Additional file 1 : Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides, the expression levels of IL-1β and TNF-α decreased within time in each group. On the other hand, IL-10 is a pro-healing cytokine, which can inhibit the function of T helper 1 (Th1) cell and reduce the production of pro-inflammatory cytokines [ 48 ]. The expression of IL-10 gradually increased over time, and iTE-scaffold group expressed higher IL-10 than NC and P-scaffold groups (Additional file 1 : Fig.…”
Section: Resultsmentioning
confidence: 99%
“…PDLSCs were cultured with EGM-2 (Lonza, Walkersville, USA) on different membranes for 7 days. In vitro angiogenic capacity was assessed by the tube formation assay on Matrigel (354230, Corning, NY, USA) as before [ 48 ]. PDLSCs in EGM-2, PDLSCs on P-scaffold, PDLSCs on iTE-scaffold and HUVECs were collected and resuspended in the medium of EGM-2.…”
Section: Methodsmentioning
confidence: 99%
“…Since the nerve blood vessels in the pulp cavity provide nutrition for the hard tissue of the tooth and guide the development of the tooth root, more and more people are beginning to realize the importance of preserving the living pulp [ 85 ]. Therefore, new technologies have emerged as time requires, such as pulp revascularization, apical induction, pulp regeneration, and so on [ 68 , 86 ]. The basis for achieving these new technologies is the development of material science.…”
Section: Pulpal Diseasesmentioning
confidence: 99%
“…Several groups have recently reported that MSCs such as adipose-derived MSCs, apical papilla mesenchymal stem cells, and dental pulp stem cells induced CD31-positive and vWF positive vasculogenic differentiation via VEGF, in addition to small molecules (e.g., VPA, forskolin). [42][43][44] Furthermore, several groups have reported that recruited MSCs or MSCs embedded in hydrogels can induce neo-vascularization in wound sites. [45][46][47] Compared to the complex structure of VEGF, VP has a short peptide sequence and therefore it is easy to produce, relatively inexpensive, and can be easily handled.…”
Section: Sp Has Been Shown To Induce Endocytosis and Recycle Nk1rmentioning
confidence: 99%